BECOMING BRIDGE-BUILDERS IN PERIODS OF TRANSITION: Towards a Communion of Civilizations in Our Times - Menamparampil, Thomas (Asian Horizons, 2012)
With the world becoming more and more globalized, we are moving into most exciting times. Economy is taking new directions, innovations in communications are bringing peoples and communities together, international solidarity offers indefinite possibilities of self expression; good ideas generated anywhere have opportunities to reach out to the remotest parts of the world; and good values preserved in any civilizational tradition can offer inspiration to persons and societies in any place on the planet. There is every possibility for cultures, civilizations, and faiths to dialogue with each other, to listen to each others’ insights, and learn from each others’ wisdom.